2015
DOI: 10.1002/rmv.1832
|View full text |Cite
|
Sign up to set email alerts
|

The bitter side of sweet: the role of Galectin-9 in immunopathogenesis of viral infections

Abstract: In recent years, a critical role for β-galactoside-binding protein, Galectin-9 (Gal-9) has emerged in infectious disease, autoimmunity, and cancer. It is a ligand for T cell immunoglobulin mucin domain 3 (Tim-3), a type-I glycoprotein that is persistently expressed on dysfunctional T cells during chronic viral infections. Gal-9 exerts its pivotal immunomodulatory effects by inducing apoptosis or suppressing effector functions via engagement with its receptor, Tim-3. Recent studies report elevation of circulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
82
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(83 citation statements)
references
References 89 publications
1
82
0
Order By: Relevance
“…Recent studies indicate that the C-CRD of Gal-9 is responsible for receptor recognition and T-cell death, while the N-CRD is more potent in activation of dendritic cells (DCs) [26]. A critical role of Gal-9 has been reported in infectious disease, autoimmune disease and cancer [27]. One identified binding partner of various glycoproteins interacting with Gal-9 is Tim-3, which is expressed on specific T-cell subsets and cells of the innate immune system, including macrophages, monocytes, and DCs [8, 28].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicate that the C-CRD of Gal-9 is responsible for receptor recognition and T-cell death, while the N-CRD is more potent in activation of dendritic cells (DCs) [26]. A critical role of Gal-9 has been reported in infectious disease, autoimmune disease and cancer [27]. One identified binding partner of various glycoproteins interacting with Gal-9 is Tim-3, which is expressed on specific T-cell subsets and cells of the innate immune system, including macrophages, monocytes, and DCs [8, 28].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in a cross-sectional cohort of patients with juvenile DM, we demonstrated that 3 proteins, galectin-9, CXCL10, and tumor necrosis factor receptor type II, can distinguish between juvenile DM patients with active disease and those in remission, with galectin-9 and CXCL10 being the most discriminative markers (26,27). CXCL10 and galectin-9 can be produced by a variety of cells, both immune and nonimmune, upon stimulation with interferons (28,29). CXCL10 has been recognized as a biomarker in several human autoimmune diseases, including myositis (29)(30)(31)(32)(33), whereas galectin-9 has been investigated mainly as a biomarker in cancer and viral infections (28,34).…”
Section: Introductionmentioning
confidence: 99%
“…CXCL10 and galectin-9 can be produced by a variety of cells, both immune and nonimmune, upon stimulation with interferons (28,29). CXCL10 has been recognized as a biomarker in several human autoimmune diseases, including myositis (29)(30)(31)(32)(33), whereas galectin-9 has been investigated mainly as a biomarker in cancer and viral infections (28,34). Reports on the role of galectin-9 in autoimmunity are conflicting, suggesting either an attenuating or an aggravating effect on autoimmune manifestations in experimental models (35,36).…”
Section: Introductionmentioning
confidence: 99%
“…A more robust and vigorous virus‐specific immune response to acute and chronic viral infections is mounted in Gal‐9–deficient mice, resulting in rapid viral clearance. Thus, antagonism of Gal‐9 signaling may be beneficial for the prevention of various infections, including viral infection , in patients with SLE.…”
Section: Discussionmentioning
confidence: 99%